2021
DOI: 10.1111/joa.13496
|View full text |Cite
|
Sign up to set email alerts
|

The humeral head: A review of the blood supply and possible link to osteonecrosis following rotator cuff repair

Abstract: Many studies have investigated the blood supply of the humeral head, and amongst these, several contradictions and inconsistences exist.Understanding and being aware of vascular anatomy and its variations is clinically relevant for several reasons: for surgeons repairing proximal humeral fractures in order to assess the vascular injury, for physicians performing diagnostic or therapeutic procedures using angiograms of these vessels and potentially also for those inclined to develop new surgical techniques (Fon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 56 publications
0
22
0
1
Order By: Relevance
“…To prevent RDON, Keough et al . highlighted the importance of avoiding damage to the vascularization of the humeral head upon arthroscopic RCR, while care should be taken not to damage the ACHA and anterolateral branch [ 7 ]. The vascular supply to the humeral head mainly involves the ACHA and posterior circumflex humeral artery [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent RDON, Keough et al . highlighted the importance of avoiding damage to the vascularization of the humeral head upon arthroscopic RCR, while care should be taken not to damage the ACHA and anterolateral branch [ 7 ]. The vascular supply to the humeral head mainly involves the ACHA and posterior circumflex humeral artery [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a study that reported that RDON could occur due to damage to the anterior circumflex humeral artery (ACHA), which is responsible for blood supply of the humeral head, depending on the location of the suture anchor. However, it was a cadaver study, not a study that analyzed actual patients [ 7 ]. Thus, owing to the lack of studies on exceptionally rare cases of humeral head osteonecrosis after arthroscopic RCR, the cause is yet to be clearly identified.…”
Section: Introductionmentioning
confidence: 99%
“…Our aim was to examine a secondary penetration during follow-up at 1 year. The secondary penetration is due to either “sinking” of the humeral head during healing of the fracture (bone necrosis or remodeling) or to severe AVN with segmental collapse of the head [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…El MR es el complejo tendinoso de cuatro músculos (supraespinoso, infraespinoso, redondo menor y subescapular) que se originan de la escápula y cuyos tendones se mezclan con la cápsula subyacente para insertarse en las tuberosidades del húmero. 6 Las funciones principales del manguito rotador son las siguientes: 7 1. Participa en la movilidad del hombro en rotaciones y abducción del húmero con respecto a la escápula.…”
Section: Anatomía Y Función Del Manguito Rotadorunclassified